Economics for the common goood: two centuries of social economic thought in the humanistic tradition - Lutz, Mark A.
Product Description This textbook presents an introduction to the central issues of social economics. Building on a venerable social economics tradition, the book recommends a more rational economic order and proposes new principles of economic policy. The issues covered include: * the inadequacy of individualistic economics in guiding the policy maker * A criticism of Economic rationality * rethinking of the modern business corporation * a critical look at markets as panacea * the harmful effects of international competition * environmental problems. The book introduces social economic concepts and challenges the reader to look beyond the confines of mainstream economic thinking to find a solution to these critical issues. From the Author This book is for some, not for others. It was a miracle that I made it through the Ph.D. qualifying exams in economic theory at Berkeley, that I managed to squeeze through a screening device that keeps people like me, who prefer qualitative to quantitative analysis, from teaching in economics departments. Subsequently, it took many more years to begin realizing just how much the basic training of young, aspiring economists ends up molding the mind and one's vision of the world. There had to be a way to recapture the lost human and social dimension, and I believe it is found in a venerable tradition that has long opposed the self-interest and mechanics-based doctrines of orthodox economics. The main purpose of this book is to introduce the interested reader to this alternative perspective and show how much it may have to offer in addressing some of the key social issues of the day. The book is divided into three parts (historical, philosophical and public policy), each trying to demonstrate the difference it makes to look at the economy from a distinctly human and social point of view. I have tried to write the present work for the educated lay person who may have some (often uncomfortable) familiarity with professed economic concepts and ways of reasoning, and who cares about the way this science (and the world) is going. Unlike other contemporary schools of alternative economics, all flirting with or embracing a postmodern approach, the book builds on an ethical foundation rooted in the logic of common sense, a common human nature, universal human rights, and an innate human dignity. It's an attempt to challenge conventional economics and the so-called economic way of thinking on grounds that are meant to be both more human and more logical. Unfortunately, the new breed of intellectual skeptics and nihilists, who like to profess that basic human rights are no more real than witches and unicorns, will find the present text epistemologically backward, narratively naive and generally less than congenial. In opposition to individualistic economics and its skeptical critics, there does exist a Common Good. To pretend otherwise is to go down the road of continuing social, spiritual and environmental decay. It seems to me the time has come for some fundamental rethinking and reorientation, and I hope this book can make a worthwhile contribution in this direction. --This text refers to the Paperback edition.